Expression pattern of osteopontin isoforms in malignant melanoma cell lines - Viktoria Koroknai; István Szász; Krisztina Jámbor; Margit Balázs (Wiley, 2024)
Abstract Osteopontin (OPN) is a secreted integrin‐binding protein that plays a role in inflammation, cellular viability, cell adhesion and migration, cancer development, and diabetes through different mechanisms. The splice variants of OPN can play essential roles in cancer development, progression, and metastasis formation; however, limited data are available about the role of OPN isoforms in human malignant melanoma. Our goal was to define the gene expression patterns of five OPN variants (OPN4, OPN5, OPNa, OPNb, and OPNc), integrin, and CD44 receptor genes in primary and metastatic melanoma‐originated cell lines (n = 19), and to explore the association of the expression patterns with clinicopathological parameters. We evaluated the invasive property of the cell lines and investigated the potential association between the invasion and gene expression of OPN isoforms. We found a significant rise in the expression of OPNc in the invasive cell lines compared to the noninvasive cells and detected significantly higher expression of the OPN splice variants in melanoma cell lines originating from more advanced stages tumors than cell lines originating from early‐stage melanomas. The correlation analysis revealed that all five OPN variants positively correlated with ITGB3 and ITGA9, whereas OPN5 positively correlated with ITGB1, ITGAV, ITGA6, and CD44. OPN can activate extracellular signal‐regulated kinase signaling through binding to α9β1 integrin, promoting melanoma tumor cell migration. It is possible that such associations between OPN splice variants and integrin receptors may play a role in melanoma progression. In conclusion, our findings suggest that high expression of OPNc correlates with the invasive behavior of melanoma cells.